Biotransformation of rice straw by Phanerachaete chrysosporium and the related ligninolytic enzymes. (28th April 2008) - Huang, Danlian; Zeng, Guangming; Peng, Zhiwei; Zhang, Panyue; Hu, Shuang; Jiang, Xiaoyun; Feng, Chongling; Chen, Yang
Biotransformation of lignin is related to the biomass utilisation of agricultural wastes. Ligninolytic enzyme from Phanerochaete chrysosporium plays an important role in biodegrading lignin and is specially concerned by researchers. The aim of the study is to optimise the conditions for producing ligninolytic enzymes in solid-state fermentation, and to biotransform the rice straw for the biomass utilisation. The effects of five factors on enzyme activity in state-solid medium were studied using orthogonal experiments, which were expected to offer reference for condition design of enzyme production in solid-state fermentation. The results indicated that the optimal condition for enzyme production by P. chrysosporium during solid-state fermentation could be realised when fungi were domesticated for 8 days, 0.8% fungi suspension (weight ratio) inoculated, temperature kept at 37?C, water content of the solid substrate maintained by 85% and 0.3% Tween80 added, respectively. Also, it was found that the temperature and water content were the foremost influencing factors for the ligninolytic enzyme production of P. chrysosporium during solid-state fermentation. The lignocellulose of rice straw was reduced significantly. The structures of the untreated straw and the straw degraded under the optimal fermentation condition were analysed through ultraviolet spectroscopy and infrared spectroscopy. It could be observed that long-bond and difficult-to-biodegrade hydrocarbons of giant molecule were degraded into short-bond hydrocarbons of small molecule, which could be easily biodegraded.